Academic Performance of the Faculty Members as Perceived by Students of the Faculty of Education at the Universities of Dongola, Gedaref - Majzoob Ahmed Mohammed; Mahgoup Elsddig Mohammed; Musa Makki Hamed; Mohammed Abdalla Dawood (University of Science and Technology, Yemen, 2017)
The aim of this study was to identify the views of students at the Faculty of Education (Universities of Dongola, and Gedaref) about the academic performance of faculty members; and to investigate the effect of some variables such as gender, level of education and age. The study used a descriptive analytical method. To achieve the aims of the study the researchers developed an instrument to measure the academic performance of the faculty members. The tool consisted of (35) items distributed over four themes. The sample of this study consisted of (150) male and female students who were selected by the stratified random sampling method. The data was then analyzed using mean, standard deviation, T-test and analysis of variance (ANOVA). Results showed that the academic performance of the faculty member was high. There was a statistically significant relationship which was positive in academic performance between students of the two universities. The results also did not indicate any statistically significant differences among the students due to the variables gender, academic level and age. Based on these findings the researchers proposed a set of recommendations. Keywords: Dongola University, Gedaref University, Academic performance.